THE FUNCTIONS OF NOUN CLAUSES IN LET’S LEARN ENGLISH TEXTBOOKS - Bonar Gurning (Muse: Jurnal of Art, 2022)
This study examines the functions of noun clauses in Let’s Learn English textbooks from the first grade until the third grade. The data are examined by using distributional method proposed by Sudaryanto (1988). The data are classified based on their functions as proposed by Quirk et al (1985). Noun clauses have nine functions, they are subject, direct object, subject complement, object complement, prepositional complement, adjectival complementation, extraposed subject, appositive, and adverbial. The result of the analysis shows that the frequencies of noun clauses in the first grade until the third grade textbooks are not stable. This will make students can not fully understand about the functions of noun clauses. Therefore, Let’s Learn English as a teaching material is inadequate in providing lesson about types and functions of noun clauses.